2015
DOI: 10.1093/nar/gkv183
|View full text |Cite
|
Sign up to set email alerts
|

H3K9 methyltransferase G9a negatively regulates UHRF1 transcription during leukemia cell differentiation

Abstract: Histone H3K9 methyltransferase (HMTase) G9a-mediated transcriptional repression is a major epigenetic silencing mechanism. UHRF1 (ubiquitin-like with PHD and ring finger domains 1) binds to hemimethylated DNA and plays an essential role in the maintenance of DNA methylation. Here, we provide evidence that UHRF1 is transcriptionally downregulated by H3K9 HMTase G9a. We found that increased expression of G9a along with transcription factor YY1 specifically represses UHRF1 transcription during TPA-mediated leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…EHMT2 is also known to be involved in neuronal plasticity16, and its expression was affected by various conditions18. Notably, recent report documented that RA, or 12- O -tetradecanoylphorbol-13-acetate (TPA), which attributes to cell differentiation in leukemic cells, activates EHMT2 along with certain transcriptional factor resulting in the suppression of target genes3536. Similar with these EHMT2 regulations, we also found that EHMT2 levels were increased after αS induction during RA treatment.…”
Section: Discussionsupporting
confidence: 77%
“…EHMT2 is also known to be involved in neuronal plasticity16, and its expression was affected by various conditions18. Notably, recent report documented that RA, or 12- O -tetradecanoylphorbol-13-acetate (TPA), which attributes to cell differentiation in leukemic cells, activates EHMT2 along with certain transcriptional factor resulting in the suppression of target genes3536. Similar with these EHMT2 regulations, we also found that EHMT2 levels were increased after αS induction during RA treatment.…”
Section: Discussionsupporting
confidence: 77%
“…The OR1N1, OR4F6, OR7A17 and OR10G2 promoter sequence were amplified from human genomic DNA using primer pairs (Supplementary Table S1). pEGFP-G9a, pCMV-Flag-LSD1, pCMV-Suv39h1, and pCMV10-Flag-KDM3B were previously described6862. Short hairpin RNAs (shRNAs) against G9a were previously described and against LSD1 and OR10G2 were designed using the siRNA sequence designer software (Clontech)6.…”
Section: Methodsmentioning
confidence: 99%
“…G9a knockout mice marked with dramatically reduced H3K9 methylation, exhibited severe growth defects in early development23. G9a also attenuates DNA methylation levels through the suppression of ubiquitin-like with PHD and ring finger domains 1 (UHRF1) which plays an essential function to maintain DNA methylation during HL-60 differentiation456. In HL-60 cells, G9a represses Janus kinase 2 (JAK2), the catalyst of H3Y41 phosphorylation, resulting in the inhibition of JAK2-H3Y41P-HP1α pathway-mediated leukaemogenesis78.…”
mentioning
confidence: 99%
“…27,56 G9a overexpressing cells progress faster into the S phase, and, conversely, G9a knockdown leads to lower S phase cells compared with controls. 27,57 In cultured myoblasts, G9a promotes proliferation via 2 different mechanisms. First, consistent with its repressor role, G9a mediates H3K9me2 marks at promoters of cell cycle inhibitors such as p21 and Rb1 in a methylation-dependent manner.…”
mentioning
confidence: 99%
“…Downregulation of UHRF1 led to a delay in S phase progression, thereby preventing tumor progression in leukemic cells. 57 Thus, the effects of G9a may be cancer specific.…”
mentioning
confidence: 99%